The sex life aquatic: sexually dimorphic scale mechanoreceptors and tactile courtship in a sea snake Emydocephalus annulatus (Elapidae: Hydrophiinae). (7th June 2021) - Crowe-Riddell, Jenna M; Jolly, Chris J; Goiran, Claire; Sanders, Kate L
Abstract: Evolutionary transitions from terrestrial to aquatic habitats involve major selective shifts in animal signalling systems. Entirely marine snakes face two challenges during underwater social interactions: (1) finding mates when pheromones are diffused by water currents; and, once a mate is located, (2) maintaining contact and co-ordinating mating when tactile cues are diminished by buoyancy force. We explore the potential tactile roles of scale protuberances in the mating of turtle-headed sea snakes [ Emydocephalus annulatus (Hydrophiinae)] by investigating sexual dimorphism in museum specimens ( N = 59). In addition to the previously noted rostral spine on the snout, we found that mature males have enlarged structures located on the chin (genial knobs) and near the cloaca (anal knobs). Ultrastructural data indicates that the rostral spine is comprised of thickened epidermal and dermal layers, similar to rugosities on the body, and likely provide stimulation to the female during prodding by the male. In contrast, the genial and anal knobs have dermally derived central cells indicative of enlarged scale mechanoreceptors (i.e. sensilla). We suggest that these mechanoreceptors are critical to mating success: genial knobs may help amorous males orient to the direction of female motion; whereas, and anal knobs likely give somatosensory feedback for cloacal alignment